Is tumour-expressed aminopeptidase N (APN/CD13) structurally and functionally unique? - Barnieh, Francis M.; Loadman, Paul M.; Falconer, Robert A. (Biochimica et biophysica acta. Reviews on cancer, 2021)
Aminopeptidase N (APN/CD13) is a multifunctional glycoprotein that acts as a peptidase, receptor, and signalling molecule in a tissue-dependent manner. The activities of APN have been implicated in the progression of many cancers, pointing toward significant therapeutic potential for cancer treatment. However, despite the tumour-specific functions of this protein that have been uncovered, the ubiquitous nature of its expression in normal tissues as generally reported remains a limitation to the potential utility of APN as a target for cancer therapeutics and drug discovery. With this in mind, we have extensively explored the literature, and present a comprehensive review that for the first-time provides evidence to support the suggestion that tumour-expressed APN may in fact be unique in structure, function, substrate specificity and activity, contrary to its nature in normal tissues. The review also focuses on the biology of APN, and its “moonlighting” functional roles in both normal physiology and cancer development. Several APN-targeting approaches that have been explored over recent decades as therapeutic strategies in cancer treatment, including APN-targeting agents reported both in preclinical and clinical studies, are also extensively discussed. This review concludes by posing critical questions about APN that remain unanswered and unexplored, hence providing opportunities for further research.